Actualizing the Local Wisdom of the Betawi Community through the Utilization of Digital Era Technology - Gandhi Seputra Nur; George Stanlei Kristanto; Jeane Abigail Reza Hardian; Jonatan Edward S; Naizha Putri Mandala (International Journal Labs, 2025)
This research aims to examine the influence of Artificial Intelligence (AI) on Betawi culture in Indonesia, by exploring the potentials and challenges faced in the preservation and development of this culture in the digital era. This study found that the integration of AI in Betawi cultural traditions can have positive impacts such as reviving Betawi indigenous culture that has begun to fade with cultural modernization, expanding the reach of the community to be able to understand more deeply Betawi cultural customs, and strengthening Betawi cultural identity. This research proves that AI has an important role in the preservation and development of Betawi culture, but it needs to be supported by critical thinking and awareness skills, as well as considerable cost capital in its use to avoid negative impacts and maximize its benefits.